Growth and Yield of Watercress (Nasturtium officinale R.Br) at The Level and Different Type of Nitrogen Fertilizer - Widaryanto, Eko; Firda N. I. K., Yulita (PLANTROPICA: Journal of Agricultural Science, 2016)
Watercress (Nasturtium officinale R.Br) is family of Brassicaceae. Watercress has become favourite of many people in Indonesia especially in Malang and used as medicinal plant. Growth and yield of watercress was affected by nutrient content of Nitrogen. Nitrogen isessensial nutrient needed by plant to growth and to form vegetive organ as leaf, branch and root. This research aims to get best level at different type of fertilizer for growth and yield of watercress by using urban farming methode. The reseach was conducted in CV. Kurnia Kitri Ayu Farm Malang from July until December 2016. The reseach used Complete Randomized Design (CRD) involving four level of dose (1, 2, 3 and 4 g/pot) and two type of different fertilizer (Urea and ZA) with four types of doses and three replicatiosn. The result showed there was an influence between the level and different type of fertilizer. Urea fertilizer on doses 4 g per pot has higher result than others treatment of variant doses of Urea fertilizer and alsoZA fertilizer on doses 4 g per pot has higher result than others treatment of doses ZA fertilizer.The yield data showed if using Urea on doses 4 g per pot increased 50% higher than ZA fertilizer on doses 4 g per pot. The result clearly indicated that 4 g per pot of Urea fertilizer was the best level of doses of different type of fertilizer.